Chamanisme féminin « contre nature » ? Menstruation, gestation et femmes chamanes parmi les Shipibo-Conibo de l’Amazonie occidentale - Anne-Marie Colpron (Journal de la Société des Américanistes)
« Counter-natural » female shamanism? Menstruation, gestation and female shamans among the Shipibo-Conibo of Western Amazonia. Amazonian shamanism is often described as a male social role from which women are ‘naturally’ excluded because of taboos concerning the particularities of their biology, namely menstrual blood and pregnancy. However, we do find evidence of women shamans in certain Amazonian populations, such as the Shipibo-Conibo. These women practice a shamanism that is comparable to that of their male colleagues, sometimes achieving the highest states of power. As well, they exercise their art at marriageable age, thus reconciling the roles of mother and shaman. This article demonstrates, through specific case studies, how these women are not seen to be limited by their biology: much like their male counterparts, they observe taboos which permit them to surpass their bodies and reach shamanic becoming.